Maqasid Shariyyah According to al-Qaradawi in The Book Al-Halal Wa Al-Haram Fi al-Islam - Ibrahim, Basri; Wan Chik, Wan Mohd Yusof (2011)
al-Qaradawi is presently a renowned scholar in the Islamic world. He is well known for his contemporary views which are highly appreciated in answering dilemmas faced by the ummah (muslim populace). And the main reason is his empathic approach to the hardship and mundane issues beguiling the lives of Muslims. Among the main attributes that makes his fatwa or views so unique is the inclusion of maqasid shar'iyyah in issuing views befitting the realities of the modern world civilizations. This article will analyse three important aspects which are firstly the background of al-Qaradawi and its relation to the problems of ummah. Secondly the maqasid sharc iyyah principles applied in his views and writings on various issues and topics. Thirdly, analyzing the use of maqasid syar'iyyah in his first writing which is al-Halal Wa al-Haram Fi al-Islam. This book is selected because it is the first writings of al-Qaradawi that took into account the maqasid shar'iyyah and is widely accepted by Muslims allover the world and reprinted 16 times by wahbah press alone. The findings of this research should prove that issues written in al-Halal Wa al-Haram Fi al-Islam did apply the maqasid shar'iyyah which is dominant in his answers to contemporary issues of the ummah. Hopefully this short research will provide a drive to the scholars in Malaysia to intensively study and understand Maqasid shar'iyyah as an important element in contemporary ijtihad.